Stenosis and stenosis-like lesions in the submandibular duct: detailed clinical and sialendoscopy-based analysis and proposal for a classification - Koch, Michael; Zenk, Johannes; Iro, Heinrich (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objective: The aim of this study was to perform a detailed analysis of submandibular duct stenoses and propose a classification for them. Study Design: This retrospective study covering the period 2001–2019 included 314 patients with 370 submandibular duct stenoses, assessed sialendoscopically for number, grade of narrowing, length, tissue type, and underlying main cause/associated diseases. Results: In the included patients, 58.9% of the stenoses were at the papilla, 89.2% were short, and 61.6% were of high grade. Predominantly inflammatory stenoses (type 1) differed from fibrotic stenoses (type 2). Detailed analysis identified stenosis-like lesions caused by anatomic duct narrowing and/or duct variations (type 3), differing significantly from type 2 stenoses in location, length, and bilaterality (each P = .0001) and from type 1 stenoses in location (P = .0001). Compared with type 2, type 1 stenoses were bilateral significantly more often and shorter (each P = .0001). Frequencies of the main causes of stenosis—anatomic narrowness/duct variation and chronic sialadenitis—differed significantly in the different locations (P = .0001). There were no significant differences in frequencies of associated diseases/conditions for the different stenosis types. Conclusions: Three types of stenosis/stenosis-like lesions were distinguished. In view of these results and the findings from a review of the literature, the location and type of stenoses were found to be more important parameters, whereas number, grade, and length were less important. The underlying cause may be useful for assessing the prognosis.
CRIS-Team Scopus Importer:2020-08-21